2021
DOI: 10.1186/s10020-021-00284-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulating brain networks associated with cognitive deficits in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a relatively well characterised neurological disorder that primarily affects motor and cognitive functions. This paper reviews on how transcranial direct current stimulation (tDCS) can be used to modulate brain networks associated with cognitive deficits in PD. We first provide an overview of brain network abnormalities in PD, by introducing the brain network modulation approaches such as pharmacological interventions and brain stimulation techniques. We then present the potential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…In addition, the different targeted cortices would yield different results (i.e., targeted to the primary motor cortex vs. to the supplementary motor area). There had been argument about the different cognition effect of tDCS on differently targeted cortex [44]. However, in the previous review of computational neuroscience modeling studies on stochastic resonance, the "neural noise" produced by tDCS, either in forms of depolarization or hyperpolarization in different cortex, can indeed improve cognitive performance [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the different targeted cortices would yield different results (i.e., targeted to the primary motor cortex vs. to the supplementary motor area). There had been argument about the different cognition effect of tDCS on differently targeted cortex [44]. However, in the previous review of computational neuroscience modeling studies on stochastic resonance, the "neural noise" produced by tDCS, either in forms of depolarization or hyperpolarization in different cortex, can indeed improve cognitive performance [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…There had been argument about the different cognition effect of tDCS on differently targeted cortex [44]. However, in the previous review of computational neuroscience modeling studies on stochastic resonance, the "neural noise" produced by tDCS, either in forms of depolarization or hyperpolarization in different cortex, can indeed improve cognitive performance [44,45]. To be specific, according to the neural noise hypothesis, the after-effect of tDCS might depend on the overall glutamatergic, GABAergic, dopaminergic, and serotoninergic synaptic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have demonstrated that the FC changes over time in the resting state were significantly correlated with the level of conscious state, which was often indexed by a subjective behavioral assessment, such as Coma Recovery Scale-Revised (CRS-R) (16,17). Even though some studies reported significant changes in FC caused by tDCS in stroke and Parkinson's disease, it is unclear to what extent the functional connectivity alterations would occur in MCS by administering tDCS (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Ko et al demonstrated that stimulation of the right DLPFC, which is the most “sensitive” area related to PD-cognitive deficit-related metabolic pattern (PDCP), may normalize the altered PDCP network ( Ko et al, 2014 ). In addition, non-invasive brain stimulation (NIBS) of the left DLPFC has been found to improve cognitive function in patients with PD ( Beheshti and Ko, 2021 ). The posterior division of the middle frontal gyri (PMFG, left and right) are key nodes in the DLPFC that are widely used as accessible cortical stimulation sites for NIBS ( Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%